Studia prognostyczne a jakość polityki energetycznej - Panek, Agnieszka (Forecast Studies vs. Quality of Energy Policy, 2008)
Energy policy is one of the major sections of each country's economic policy. So it is obvious that the energy policy represents the main important element of the European Union cohesion policy. The expression of understandable and acceptable goals in this area by member states, appropriate quantity adjustment of tasks and coordination of each country's activity should result in implementation of the union policy. Documents published on these areas make the base for taking decision on investments and promotion of the chosen solutions. Using of the forecast studies at the very beginning of planning process ensures success of action. The paper aims to present the importance of using forecast studies for creation of effective energy policy. Beyond doubt is that forecasts studies should be the beginning for a decision making processes which are the starting point of changes in current situation, although the long term forecasts are the huge challenge. Only few elements of forecast assumptions seem to be quite stable, for example: availability of energy sources and their size. Others like micro and macro coefficients are changing very often. All changes of economic situation have the influence on the forecast result and cause the necessity for its correction. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 320-332